Vibration analysis with young's fringes modulated speckle - Bolognini, Néstor (1980)
A new method for vibrational analysis is proposed. It is based on the deblurring of time-averaged Young's fringes inside speckle grains in the image of a vibrational object. A spatial filtered image of the recording of those speckles, modulated by Young's fringes, shows the loci of points of equal vibratory amplitude.